Carnosic acid impedes cell growth and enhances anticancer effects of carmustine and lomustine in melanoma. Issue 4 (3rd July 2018) - Lin, Kun-I; Lin, Chih-Chien; Kuo, Shyh-Ming; Lai, Jui-Chi; Wang, You-Qi; You, Huey-Ling; Hsu, Mei-Ling; Chen, Chang-Han; Shiu, Li-Yen
Abstract : Carnosic acid (CA), a major polyphenolic diterpene present in Rosmarinus officinalis, has been reported to have multiple functions, including antitumor activity. The MTT assay, BrdU incorporation, wound healing, and colony formation were used to detect melanoma B16F10 cell growth and proliferation. Flow cytometry was used for cell cycle detection. p21 and p27 expression was detected by Western blotting. B16F10 cell xenograft model was established, and treated with CA, carmustine (BCNU), or lomustine (CCNU). The present study found that CA exhibits significant growth inhibition and cell cycle arrest in melanoma B16F10 cells. We also found that CA triggers cell cycle arrest at G0 /G1 phase, and enhances p21 expression. Additionally, CA can enhance BCNU- and CCNU-mediated cytotoxicity and cell cycle arrest in B16F10 cells. Finally, we found that CA inhibits tumor growth, and reduces the values of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in vivo . The present study study concluded that CA may be safe and useful as a novel chemotherapeutic agent.